DIATOM STRATIGRAPHY OF MANGROVE ECOSYSTEMS ON THE NORTHERN COAST OF CENTRAL JAVA - Tri Retnaningsih Soeprobowati; Sri Widodo Agung Suedy; Peter Gell (JOURNAL OF COASTAL DEVELOPMENT, 2012)
The natural mangrove ecosystems along the Northern Coast of Central Java were very limited in extent, even had replanted almost twenty years ago. Naturally, the upper layer of sediment are the latest deposition (superposition). Environmental condition recently are recorded in the top sediment layer, and can be used to reconstruct past condition  (the present is the key to the past). The potential use of diatoms to reconstruct palaeoecology is well established. Diatoms are microscopic algae that form siliceous frustules which make them well preserved in sediment. Diatoms and their assemblages are very useful as integrated indicators of environmental changes because their distribution is closely linked to water quality parameters as well as their affinities to several physical habitats. This research was conducted in order to determine the changes of mangrove ecosystem in the Northern Coast of Central Java based on diatom stratigraphy. Sediment samples from mangrove sites were taken from Pekalongan, Brebes, Semarang, Demak and Rembang. Diatom analysis, consist of digestion, preparation, and identification. The diatom stratigraphy was performed by Software of  C2 1.5.1. Stratigraphycally, the mangrove ecosystems along the Northern Coast of Central Java were previously more influenced by freshwater rather than the marine sources which dominate today.